A health record integrated clinical decision support system to support prescriptions of pharmaceutical drugs in patients with reduced renal function: Design, development and proof of concept. Issue 6 (June 2015) - Shemeikka, Tero; Bastholm-Rahmner, Pia; Elinder, Carl-Gustaf; Vég, Anikó; Törnqvist, Elisabeth; Cornelius, Birgitta; Korkmaz, Seher
Highlights A real time CDSS developed to support prescriptions of drugs in patients with renal insufficiency. Tested in hospital and outpatient settings. Well received in both settings. Some elements used to a limited extent. Increases the attention on patients with renal insufficiency.